Delayed disengagement of attention from snakes in children with autism - Isomura, Tomoko; Ogawa, Shino; Shibasaki, Masahiro; Masataka, Nobuo (Frontiers in Psychology, 2015)
In the visual search task, it is well known that detection of a tilted straight line as the target among vertical lines that act as distractors is easier than vice versa, and that detection of a snake image as the target among flower images is easier than vice versa. In this study, the degree of such search asymmetry was compared between 19 children with autism and 14 typically developing (TD) children. The results revealed that compared to TD children, children with autism were disproportionally slow when asked to detect the flower among the snake images, suggesting the possibility that they experienced difficulty of disengaging their attention from the snake images. This delayed disengagement would serve itself as an enhanced attentional bias toward snakes in children with autism that is similar to characteristics of visual search performance in anxiety patients.